Thermal energy grid storage: Liquid containment and pumping above 2000 °C. (15th February 2022) - Amy, Caleb; Pishahang, Mehdi; Kelsall, Colin; LaPotin, Alina; Brankovic, Sonja; Yee, Shannon; Henry, Asegun
Highlights: Inert containment of large thermal systems appears feasible and economical. Graphite foil can be used to seal liquids at 2300 °C. Metallurgical grade silicon can be contained at 2300 °C. Low grade pressed graphite can contain silicon at 2300 °C. Silicon alloys containing 67% iron by mass can be contained at 1700 °C. Affordable silicon can be pumped above 2000 °C using an all graphite infrastructure. Abstract: As the cost of renewable energy falls below fossil fuels, the key barrier to widespread sustainable electricity has become availability on demand. Energy storage can enable dispatchable renewables, but only with drastic cost reductions compared to current battery technologies. One electricity storage concept that could enable these cost reductions stores electricity as sensible heat in an extremely hot liquid (>2000 °C) and uses multi-junction photovoltaics (MPV) as a heat engine to convert it back to electricity on demand, hours or days, later. This paper reports the first containment and pumping of silicon in a multipart graphite tank above 2000 °C, using material grades that are affordable for energy storage at GWh scales. Low cost molded graphite with particle sizes as large as 10 μm successfully contained metallurgical grade silicon, even with as much as two-thirds iron by mass for up to 10 h and temperatures as high as 2300 °C, in tanks as large as two gallons.